Synthesis and bioactivity evaluation of 2-aza-anthraquinones - Tuyen, Nguyen Van; Chinh, Pham The; Thuy Giang, Le Nhat; Thu Ha, Vu Thi; Tuyet Anh, Dang Thi; Phuong, Hoang Thi; Thanh, Nguyen Ha; Tham, Pham Thi; Trung, Nguyen Quang (Vietnam Journal of Chemistry, 2016)
2-Aza-anthraquinones can be found in nature. Many of these azaanthraquinones derivatives have indeed been discovered to possess diverse and pronounced biological activities, including antimicrobial, antiparasitic, antiviral and anticancer properties. These compounds have been shown to be an intercalating agent to DNA. In continuation of our synthetic interest in physiologically active quinone derivatives, the present report describes the synthesis and bioactivity evaluation of 2-aza-anthraquinones. The biological assessment of all these compounds demonstrated a significant cytotoxic effect of 2-azaanthraquinones against different cancer cell lines